Factors associated with exercise capacity in patients with a systemic right ventricle. (1st October 2019) - Gavotto, Arthur; Abassi, Hamouda; Rola, Matthieu; Serrand, Chris; Picot, Marie-Christine; Iriart, Xavier; Thambo, Jean-Benoit; Iserin, Laurence; Ladouceur, Magalie; Bredy, Charlene; Amedro, Pascal
Abstract: Background: Systemic right ventricle (RV) is a rare and complex congenital heart disease (CHD). Patients with a systemic RV present with a significant decrease of their exercise capacity. We aimed at identifying clinical and paraclinical factors associated with maximum oxygen uptake (VO2max ) in adults with a systemic RV. Methods: This multicentre cross-sectional study was performed in 2017 in three French tertiary care CHD centres. Adult patients with a D-transposition of the great artery (d-TGA) or a congenitally corrected TGA (cc-TGA) were included. Demographic, clinical, laboratory and imaging data were collected. Univariate and multivariate analyses were performed to identify predictors of impaired VO2max, as measured by cardiopulmonary exercise test (CPET). Results: A total of 111 patients were included in the study (85% d-TGA, median age 37.2 ± 8.2 years). Most patients presented with impaired physical capacity (mean VO2max of 23.3 ± 6.9 ml/kg/min, representing 68.4 ± 16.6% of predicted values) and ventilatory anaerobic threshold (VAT) impaired (mean VAT of 32.7 ± 10.9% of the predicted values). In univariate analysis, VO2max correlated with professional status, NYHA functional class, BNP level, the type of systemic RV, decreased RV function values in cardiac imaging, the severity of tricuspid regurgitation, the presence of a pacemaker or an implantable defibrillator, the VAT, the maximum load, and the maximal heart rate during exercise. In multivariate analysis, the VO2max remained associated with the NYHA functional class. The final multivariate model explained 49% of the variability of VO2max . Conclusion: NYHA functional class and RV function are predictors of impaired exercise capacity in adult patients with systemic RV. Highlights: Patients with a SVR present with a significant decrease of their exercise capacity. Determinants of VO2max in these patients have not been fully identified. SVR patients presented with impaired VO2max and muscular deconditioning. NYHA functional class remains the strongest predictor of impaired exercise capacity in SVR patients.